OPTIMIZATION OF THE EDUCATIONAL PROCESS AT THE DEPARTMENT OF GENERAL SURGERY - Okhunov, A.O.; Khudaiberganova, N.Sh.; Kasimov, U.K.; Atakov, S.S.; Bobabekov, A.R.; Boboev, K.; Abdurakhmanov, F. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
This article outlines the improvement of the regulatory and legal framework in the field of training medical personnel with the implementation of methodological guidance of medical educational institutions, as well as the system of postgraduate education, advanced training and retraining of specialists for the healthcare system today is a priority task of reforming the medical education system in the Republic Uzbekistan. The entire educational process consists of various educational blocks and is based on the principle of "single day of surgery". The work begins with a lecture on the topic being covered and continues in two main directions - theoretical and practical in a 50/50 ratio. At the same time, an important attribute of this approach is the continuation of the educational process into work practice, which is based on the application of the traditional principle of “learning at the bedside of the patient”. The proposed recommendations can be used in the organization of the educational process in the system of medical education, including in the system of advanced training and professional retraining.